2014
DOI: 10.1016/s1474-4422(13)70282-5
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody titres at diagnosis and during follow-up of anti-NMDA receptor encephalitis: a retrospective study

Abstract: Summary Background We aimed to assess the sensitivity/specificity of serum and CSF antibody-testing in patients with anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, and the correlation between titers, relapses, outcome, and epitope repertoire. Methods In this observational study, brain immunohistochemistry and cell-based assays (CBA) with fixed and live NMDAR-expressing cells were used to determine the sensitivity/specificity of antibody-testing in paired serum/CSF obtained at diagnosis of 250 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
766
14
33

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 799 publications
(844 citation statements)
references
References 39 publications
31
766
14
33
Order By: Relevance
“…By reconstructing functional autoantibodies from CSF cePc in the form of rhuMab, we demonstrate the presence of a CNS‐specific antigen‐driven humoral immune response in the CSF compartment of patients with anti‐NMDAR encephalitis, consistent with studies showing that the sensitivity of NMDA receptor antibody testing is higher in CSF than in serum and CSF antibody levels correlate with the course of the disease 5. Whether autoreactive B‐cell affinity maturation indeed occurs inside the CNS compartment and some of the clonally related B cells migrate to the peripheral system to produce self‐reactive antibodies, or CNS‐specific B‐cell clones transmigrate the BBB and proliferate in the “B‐cell friendly” environment of the CNS, remains to be elucidated in further studies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…By reconstructing functional autoantibodies from CSF cePc in the form of rhuMab, we demonstrate the presence of a CNS‐specific antigen‐driven humoral immune response in the CSF compartment of patients with anti‐NMDAR encephalitis, consistent with studies showing that the sensitivity of NMDA receptor antibody testing is higher in CSF than in serum and CSF antibody levels correlate with the course of the disease 5. Whether autoreactive B‐cell affinity maturation indeed occurs inside the CNS compartment and some of the clonally related B cells migrate to the peripheral system to produce self‐reactive antibodies, or CNS‐specific B‐cell clones transmigrate the BBB and proliferate in the “B‐cell friendly” environment of the CNS, remains to be elucidated in further studies.…”
Section: Discussionsupporting
confidence: 79%
“…Irrespective of the trigger of anti‐NMDAR encephalitis, data from previous studies suggested an enhancement of the immune response within the CNS, with potential antigen‐driven affinity maturation and clonal expansion of plasma cells 16. This hypothesis was suggested by three findings, (1) a frequent intrathecal synthesis of NMDAR antibodies even early in the disease course,1 (2) biopsy and autopsy material from patients showing brain inflammatory infiltrates containing plasma cells,6, 7 and (3) the better correlation of the course of the disease with CSF antibody titers than with serum antibody titers 5. All four treatment‐naive patients with recent onset anti‐NMDAR encephalitis in the current study showed intrathecal B‐cell and plasma cell accumulation and intrathecal production of NMDAR‐specific IgG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaporin‐4‐IgG, the effector of neuromyelitis optica spectrum disorders, is detected in serum more readily than in cerebrospinal fluid,7 but some intrathecal production of aquaporin‐4‐IgG occurs 8. In contrast, NMDAR‐IgG is detected more readily in the CSF,9 despite at least some NMDAR‐IgG production in peripheral immune responses 10. Preliminary data by Irani et al.…”
Section: Introductionmentioning
confidence: 98%
“…Escalation to a CyBorD regimen was also not effective in improving mRS scores. Decrease in the serum and CSF antibody titers of more than twofold, considered as a substantial change,21 were not achieved after 2 cycles of bortezomib in any of the patients.…”
Section: Discussionmentioning
confidence: 79%